Ultrasonic Distance Measurement - SR, Reeja; Sriram, Venkat Durga; Reddy, Tarun R; Venkatamanu, Venkatamanu (International Journal of Computer Sciences and Engineering, 2025)
Measuring distance of an obstacle in the direction of a person, stationary or moving object is important parameter. Measuring the distance using ultrasonic sensors is one of the cheapest among various options. In this paper measuring distance of an obstacle in the direction of a person done by ultrasonic sensor. 40 kHz ultrasonic transducer is used for scaling the outpost between obstacle and the person. Ultrasonic sensor with a microcontroller it calibrates the distance which is displayed on an android device connected via Bluetooth. An android application displays the distance in various scaling units. The scaling units are Centimetre, Meter, Inches, Yards, Foot